Surgical Ethics: Ethical Challenges and Practices in Traditional and Emerging Technologies - Hao SUN; Hongjiang SONG (Yixue yu zhexue)
This study systematically analyzes prominent ethical challenges in contemporary surgical practice, focusing on critical issues including the excessive expansion of surgical indications, superficial implementation of safety protocols, and imbalanced benefit-risk evaluations. It conducts an in-depth investigation into the technical incentives, administrative pressures, and decision-making biases underlying these phenomena. Particularly under the widespread deployment of surgical robotics, emerging dilemmas requiring urgent resolution have surfaced: the progressive marginalization of physicians' clinical roles, erosion of patient informed consent protections, ambiguity in liability determination, and institutional inertia in ethical governance frameworks. In response, the authors propose a surgical ethics framework emphasizing five core principles: patient welfare supremacy, transparent risk-benefit disclosure, multidimensional competency development for surgeons, equitable allocation of medical resources, and adaptive evolution of ethical standards. This conceptual architecture aims to establish theoretical foundations and operational guidelines for harmonizing ethical system construction with technological advancement in modern surgery.